Answer:
(0,7)
Step-by-step explanation:
(I'm assuming you have to solve the system of equations)
3x -10y = -70
4x +9y = 63
Solving by elimination.
Eliminate x first, so we need the x-component of both equations to have the same number but opposite sign. So i'm going to multiply the first by -4 and the second by +3.
//I could have also done +3 to first and -4 to second
-4(3x -10y = -70)
3(4x +9y = 63)
-12x +40y = 280
12x +27y = 189
Add the equations //x's cancel
67y = 469
Divide both side by 67, y=7
Plug in y into any original equation to solve to x
3x - 10(7) = -70
3x -70 = -70
3x = 0
x=0